Development Of Zn-Mn02 Battery Using Chitosan-Znci2. Gel Polymer Electrolytes. - Mohamad, Ahmad Az'min; Aziz, Azizan (Universiti Sains Malaysia, 2007)

(untitled)
This project is divided into two main sections, that is to produce solid polymer electrolyte (SPE) as a proton conductor (H+) and to fabricate polymeric solid-state protonic battery with configuration of zinc (Zn)/SPE/manganese (IV) oxide (Mn02)' 1.0 g of chitosan was dissolved in 100 ml of 1 % acetic acid solution.